EFEKTIVITAS MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA IPS MAN 1 SAMARINDA - Nurlaela; Umi Fitria; Seto Indarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to analyze the effectiveness of the Jigsaw cooperative learning model in improving learning outcomes in Social Studies in grade XI. The Jigsaw model focuses on group learning. In the Jigsaw learning model, there are home groups and expert groups. The home group is a combination of several expert groups. This model is one of the approach strategies that is widely used. to improve the quality of classroom learning and encourage students to work together and provide more active opportunities in the learning process. This is implemented as an alternative to conventional teacher-centered learning and less active student involvement. The research approach uses a quantitative quasi-experimental sample of 70 social studies students of class XI MAN 1 Samarinda divided into experimental and control classes. Data were collected through pretests and posttests as well as questionnaires to determine student learning outcomes. This analysis uses the t-test to calculate differences in student learning outcomes before and after the use of the Jigsaw method and to compare learning outcomes between the experimental and control classes. The results showed that there were differences in social studies learning outcomes between students taught the Jigsaw learning model and conventional learning. The calculated t-value = 4.28 with df = 4 and p-value <0.05 (significant). There is a significant difference between the pretest and posttest. There is a statistically significant difference between the scores before and after treatment. The average score increased by 8 points after treatment.